Data for: Andic soil properties and tephra layers hamper C turnover in Icelandic peatlands - selective dissolution of Al, Fe, Si and decomposition proxies - Möckel, Susanne Claudia; Erlendsson, Egill; Gísladóttir, Guðrún (Zenodo, 2022)
Due to frequent volcanic activity and erosion of dryland soils, peatlands in Iceland receive regular additions of mineral aeolian deposits (tephra and eroded material). Therefore, their soils may develop not only histic, but also andic characteristics. Here we present data sets of a study that elucidates interactions between carbon characteristics and andic soil properties in Histosols of three Icelandic peatlands. The data sets contain information about the soil carbon structure derived by 13 C NMR spectroscopy, andic soil properties based on selective dissolution of Al, Fe and Si, decomposition proxies C/N, δ 13 C and δ 15 N, information on total carbon and nitrogen content, dry bulk density, soil organic matter content and pH measured in deionised water and NaF solution. DATA-SPECIFIC INFORMATION FOR: Moeckel et al 2021_andic soil properties_decomposition proxies.xlsx 1. Number of variables: 20 2. Number of observations: 45 soil samples 3. Variable List: The table shows raw data of: - Selective extraction of aluminum (Al), silicon (Si) and iron (Fe) with ammonium oxalate (Al o , Fe o , Si o ) reported in g kg -1 . - Selective extraction of Al and Fe with sodium pyrophosphate (Al p , Fe p ) reported in g kg -1 . - Al o +0.5*Fe o , allophane and ferrihydrite reported in %. - Al p /Al o and Fe p /Fe o ratios. - Phosphate retention (P-ret.) reported in %. - Total carbon (C) and nitrogen (N), reported in %. - C/N ratio. - Stable isotope ratios δ 15 N and δ 13 C, reported in ‰. - Dry bulk density (DBD) reported in g cm -3 . - Soil organic matter content (SOM) reported in %. - pH measured in deionised water (pH H2O ) and in 1N NaF solution (pH NaF ) DATA-SPECIFIC INFORMATION FOR: Moeckel et al 2021_13C NMR.xlsx 1. Number of variables: 2 2. Number of observations: 45 soil samples 3. Variable description: The data tables show results of 13 C NMR spectroscopy of 45 soil samples, i.e. the chemical shift (ppm) and the according relative intensity (%). Funding provided by: Icelandic Research Fund of The Icelandic Centre ...